Cottonseed: A sustainable contributor to global protein requirements. (May 2021) - Kumar, Manoj; Tomar, Maharishi; Punia, Sneh; Grasso, Simona; Arrutia, Fátima; Choudhary, Jairam; Singh, Surinder; Verma, Pooja; Mahapatra, Archana; Patil, Sharmila; Radha; Dhumal, Sangram; et al.
Abstract: Background: Cottonseed is a sustainable source of plant protein, producing ~10 million metric tons of protein globally. This protein has the potential to fulfil the annual protein requirement of more than half a billion people globally. Its functional properties have established the potential of cottonseed protein (CSP) as a candidate for alleviating malnutrition in the Asian and African continents. Regardless of these quality attributes, the inherent association of gossypol with CSP makes it unsuitable for direct human consumption due to its toxicity. Scope and approach: The present review elaborates on physical, chemical and biological methods for enhancing the quality and suitability of CSP for human nutrition by reducing the gossypol content to permissible limits (450 ppm) per the U.S. Food and Drug Administration and World Health Organization. Amino acid profiling, functional property (water holding capacity, oil holding capacity, foaming properties, emulsification characteristics, and protein solubility), in vitro protein digestibility and molecular weight analyses are the parameters considered important for the application of CSP in foods. This review also highlights the diverse applications of CSP directly in human nutrition or indirectly as animal protein. Key findings and conclusions: Degossypolyzation is mainly performed by solvent extraction, although gamma irradiation and the use of microorganisms are gaining momentum. CSP is a good candidate for use in food and feed formulations, with a balanced amino acid composition and functional properties comparable to those of soy protein. Integration of both chemical and biological methods might prove to be more efficient for degossypolization and improving the utilization of CSP for human nutrition. Highlights: Physical, chemical, and biological methods for improving utilization of cottonseed as protein source. Solvent extraction remains the method of choice. Functional properties and amino acid profile for evaluation of quality of cottonseed protein are well discussed. Application of cottonseed protein as direct and indirect source of supplement in human nutrition. Food safety and regulatory issues for application of cottonseed protein/flour in foods is outlined in the review.